AGE REVERSAL- A NEW PARADIGM SHIFT IN MEDICAL SCIENCES - Binafsha Manzoor Syed (Liaquat Medical Research Journal, 2023)
Ageing is a physiological phenomenon; all living beings in the universe are born with a default setting. Ageing is associated with several morbidities, chronic illness, and eventual demise. For a long time, ageing was thought to be a genetic portent, but recent research suggests more epigenetic involvement. Animal model research has shown successful reversal of ageing. Remodelling of the genome to the younger age will likely eliminate senile diseases.